Implementation of structured feedback in a psychiatry residency program in Canada: a qualitative analysis study - Thakur, Anupam; Darani, Shaheen; Kalocsai, Csilla; Silver, Ivan; Sockalingam, Sanjeev; Soklaridis, Sophie (Frontiers in Psychiatry, 2023)
Structured feedback is important to support learner progression in competency-based medical education (CBME). R2C2 is an evidence-based four-phased feedback model that has been studied in a range of learner contexts; however, data on factors influencing implementation of this model are lacking. This pilot study describes implementation of the R2C2 model in a psychiatry CBME residency program, using the Consolidated Framework for Implementation Research (CFIR).The study was carried out in three phases: planning, implementation and evaluation. After receiving training, 15 supervisors used the R2C2 feedback model with residents. Semi-structured interviews explored (n=10) supervisors' experience of the model. CFIR was used to identify factors that influence implementation of the R2C2 model when providing feedback to residents.Qualitative data analysis revealed fourthree key themes: Perceptions about the R2C2 model; Facilitators and barriers to its implementation, and Fidelity to R2C2 model and Intersectionality.The CFIR implementation domains provided structure to the themes and subthemes.The R2C2 model is a helpful tool to provide structured feedback. Structure of the model, selfefficacy, in-house educational expertise, learning culture, organizational readiness, and training support are important facilitators of implementation. Further studies are needed to explore the learner's perspective and fidelity of this model.